The Relationship Between Online Game Addiction And Depression Tendencies In Indonesian Adolescents: Online Game Addiction And Depression Tendencies - Hanu Khansa Zabrina (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: This study aims to determine the relationship between online game addiction and depression tendencies in Indonesian adolescents. Online game has become a popular entertainment activity among various ages. If online game play is played excessively and continuously without self-control, then individuals will experience in online game addiction and have negative impacts such as poor social relations with family and friends, which causes online game addicts to often be isolated from society and prone to suffering from mental disorders such as depression. Methods: This study uses a quantitative survey method. The research sample based on purposive sampling technique was conducted on 60 respondents who were Indonesian adolescents who actively played online games. The instruments used are Scales of Game Addiction for Adolescents and The Beck Depression Inventory Results: The data analysis technique used a simple linear regression test with the SPSS Statistics 25 for Windows program. The results of the linear regression analysis test indicate that there is a significant relationship between online game addiction and depression. This is evidenced by the acquisition of a simple linear regression test significance value of 0.393 (<0.05). Conclusion: The online game addiction has significant association with depression in Indonesian adolescents.